Penanganan Serangan Brute Force dan Port Scanning Pada Router Mikrotik - Deden Hardan Gutama; Rahmad Arif Setiawan; Adhien Kenya Anima Estetikha (Himpunan Penggiat Teknologi Informasi Abrar Indonesia, 2022)
In maintaining the integrity and validity of data, security on an agency's network is one of the urgencies that must be considered. In order to guarantee services that are always available to users. The systems used to detect intruders on a network in the 4.0 era are generally able to detect various types but have not been able to take preventive action, but from a user perspective, users really need information technology and this is one of the causes of security cases in Indonesia. a network is increasing every year where this happens because of the low concern of the organization on the security of a network. Therefore we need a system that is able to make it easier for network administrators to monitor network traffic with an Intrusion Prevention System (IPS).